IMPLEMENTASI SISTEM MANAJEMEN PEMBELAJARAN (LEARNING MANAGEMENT SYSTEM) DALAM PENGEMBANGAN PROFESIONAL BERKELANJUTAN (CONTINOUS PROFESSIONAL DEVELOPMENT) GURU - Setiaji Aji (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The development of interconnected network (internet) technology has led to various new applications, including applications for education. One of the benefits of internet technology in the field of education is as a learning tool, namely learning management system (LMS). The aims of this research namely determine the implementation of school LMS in the continuous professional development of vocational school teachers. Collecting data using a questionnaire with google form, via WhatsApp, semi-structured interviews, and documentation. Method research using a quantitative descriptive approach with analysis Structural Equation Modeling approach using Smart Partial Least Square software. The sample in this study were 75 productive teachers in the field of electrical engineering expertise and electronics engineering expertise in 4 SMK N Bandung, namely SMK N 4 Bandung, SMK N 6 Bandung, SMK N 8 Bandung and SMK N PU Bandung. The research results show school support has a positive and significant effect on self-development. Technical support has a positive and insignificant effect on self-development. and Self-efficacy has a positive and significant effect on teacher self-development. The problems that occur in the implementation of the school LMS can be categorized into 3 factors, namely 1) the school support factor, 2) the technical support factor, and 3) the teacher factor. The implementation of school LMS is very helpful in the self-development of vocational teachers who have the ability to produce graduates in accordance with the demands of the 21st century workforce, namely workers who have 4C skills or abilities, critical thinking and problem solving, creative and innovative, communication, and collaboration